ANNEALING OF UNFERMENTED (POLVILHO DOCE) AND FERMENTED (POLVILHO AZEDO) CASSAVA STARCHES - GOMES, ANIDA MARIA MORAES; SILVA, CLÁUDIO ERNANI MENDES DA; SILVA, PALOMA LIMA DA; SILVA RICARDO, NÁGILA MARIA PONTES; GALLÃO, MARIA ISABEL (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2010)
The effects of annealing on the properties of unfermented (polvilho doce-PD) and fermented (polvilho azedo-PAD) cassava starches were studied. The samples were submitted to annealing treatment for 24, 72, 96, 144, 192 and 240 hours. The annealing treatment changed the main physicochemical (gelatinization, enthalpy and temperature) and rheological properties (swelling power, peak viscosity and pasting temperature) of the both samples. The increase in the gelatinization temperatures and the narrowing of the gelatinization range was attributed to an reinforcement in the packing of the double helices of the amylopectin. The PAD samples seemed to be more affected by this treatment than PD ones. The PAD samples presented some characteristics of a waxy starch, such as increased crystallinity and increased stability of the pastes, which from a technological point of view is very important to diversify further its use in the food industry.